2022
DOI: 10.3390/agronomy12050995
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Performance of Chickpea Affected by Drought Stress at Different Growth Stages

Abstract: Susceptibility to drought stress has restrained chickpea productivity at a global level, and the development of drought-tolerant varieties is essential to maintain its productivity. Therefore, the present study was conducted to evaluate genetic divergence in selected genotypes of chickpea and their morpho-physiological responses under irrigated and stressed conditions to identify the traits that account for the better performance of these genotypes under stressed conditions, as well as genotypes with improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 38 publications
2
11
1
Order By: Relevance
“…The vegetative stage manages the overall phenotypic expression of coriander and prepares for the upcoming reproductive phase. However, in the case of this study, we found that the most sensitive stage of growth with respect to drought stress regimes (MS75 AND SS50) was the seed filling stage (Sachdeva et al, 2022). The amount of reduction of plant and leaf fresh and dry biomass was greater and significant (p ≤ 0.05) during the seed filling stage rather than the bolting and vegetative stages (Khatun et al, 2021) as indicated in Figures 5, 6, while shoot fresh and dry biomass showed non-significant results.…”
Section: Discussioncontrasting
confidence: 59%
“…The vegetative stage manages the overall phenotypic expression of coriander and prepares for the upcoming reproductive phase. However, in the case of this study, we found that the most sensitive stage of growth with respect to drought stress regimes (MS75 AND SS50) was the seed filling stage (Sachdeva et al, 2022). The amount of reduction of plant and leaf fresh and dry biomass was greater and significant (p ≤ 0.05) during the seed filling stage rather than the bolting and vegetative stages (Khatun et al, 2021) as indicated in Figures 5, 6, while shoot fresh and dry biomass showed non-significant results.…”
Section: Discussioncontrasting
confidence: 59%
“…Reduced chickpea yield under water stress largely results from pod abortion and impaired pod filling, which seem to occur as soon as water deficits start to develop, regardless of plant phenology (Leport et al, 2006; Randhawa et al, 2014). Root traits, such as root length, root biomass and RS ratio, are usually correlated with higher chickpea yield under water stress by facilitating water mining through and minimising transpiration (Kumar et al, 2012; Kashiwagi et al, 2015; Ramamoorthy et al, 2016; Ranjan et al, 2022; Sachdeva et al, 2022). However, this association does not always occur (Serraj et al, 2004; Kashiwagi et al, 2005; Zaman‐Allah et al, 2011a), likely due to differences in the experimental setup and plant genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Among the irrigation levels, D1 (Irrigation at 30 DAS and flower initiation) required the highest (81.57 DAS) number of days for pod formation followed by D2 (Drought stress at flowering up to physiological maturity) at 79.27 DAS. Sachdeva et al [12], indicated that water stress during the reproductive stage leads to a significant reduction in both plant yield and yield-related traits.…”
Section: Effect Of Foliar Spray Of Plant Growth Regulators and Nutrie...mentioning
confidence: 99%
“…Phenology plays a vital role in the adaptation of crops to various environments, and its variation depends on factors such as genotype, soil moisture, sowing time, and also geographical location [12]. Plants can mitigate the impact of terminal drought by exhibiting early phenology [3].…”
Section: Introductionmentioning
confidence: 99%